Research on the usability of space beneath urban overpasses: a case study of Shanghai - Feifei Song; Zhi Ma; Lijing Zhu (Techne, 2025)
This study examines the usability of spaces beneath overpasses in Shanghai, focusing on three sites along the Suzhou River. Using a mixed-method approach combining comparative case analysis and survey data, the research highlights the transformative potential of these underutilised urban spaces. Findings reveal that central sites with professional design interventions exhibit higher adaptability and public engagement, while peripheral sites face challenges from fragmented development. The study underscores the need for context-sensitive, community-focused strategies to integrate underpass spaces into the urban fabric, enhancing connectivity, social inclusion, and liveability.